Uprizorenje zakonodavstva u romanu A Frolic of His Own autora Williama Gaddisa - Grgas, Stipe (Array, 2003)
The author deals with the way that the Amkerican novelist William Gaddis employs law in his novel A Frolic of His Own. The contention is that the visibilityb of law in this text mirrors the significance of this discourse within the American polity. In his conclusion the author draws attention to the way that literature represents a critical intervention within the dominant discourses of society.